Motivasi Petani dalam Usahatani Buah Naga Merah (Hylocereus polyrhizus) di Desa Glagahagung Kecamatan Purwoharjo Kabupaten Banyuwangi - PANGHARIBOWO, SETO AGUNG; ANGGRENI, I GUSTI AYU AGUNG LIES; SUDARTA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
F a r m e r Motivation in Red Dragon Fruit (Hylocereus polyrhizus) Farming in Glagahagung Village, Purwoharjo Sub-district of Banyuwangi District Red dragon fruit cultivation have increased in several regions in Indonesia, especially in the island of Java in the last decade. Red dragon fruit cultivation  is said better source of income for farmers than other commodity plants that bhave been cultivated by farmers. This research is intended to find out what and how is the level of motivation offarmers in the Glagahagung village in diverting their cultivation from rice farming and palawija to red dragon fruit farming. The study uses descriptive analysis method to analyze four factors that form motivation, namely, economic need, economic environment, social need, and social environment the variable  in  this  study.  The  study suggests the motivation  of red  dragon  fruit  farmer  in Glagahagung village is at very good category with the value of 2,83 based on the average score result of four variables that form motivation. The economic need scores 2,81, economic environtment scores 2,78, social need scores 2,85 and social environment scores 2,86, from highest Likert scale that is used (3,00).